Content Adequacy of Oral Literature in Selected English Studies Textbooks: Implications for Inculcating Moral Values into In-School Adolescents - Ifeoluwa Theophilus Akinsola; Bolape Olufunto Olaosebikan (International Journal of Social Learning (IJSL), 2021)
Textbooks are essential resources in the teaching-learning process. The integration of English language and literature called English Studies at the junior secondary schools in Nigeria has brought about textbooks incorporating both language and literature (oral and written) components. This study was carried out to analyze the content adequacy of oral literature incorporated in New Oxford Secondary English Course for Junior Secondary Schools and New Concepts English Textbooks and investigate teachers' perceptions. Book one to three of the two textbooks was purposively selected because they were used in the selected junior secondary schools for this study. The study, hence, adopted a mixed-methods of data collection and analysis. The textbooks selected were content analyzed by drawing out their oral literature components. Quantitative data were collected using a self-constructed questionnaire from 50 teachers of English studies randomly selected across 25 junior secondary schools in the Ibadan metropolis. The content analysis done of the selected textbooks was compared with the teachers' perception of the adequacy of the textbooks in inculcating moral values into students. The study recommended, among others, that English teachers at the junior secondary school level should actively implement the oral literature content of the English studies textbook with the use of appropriate teaching methods, strategies, and instructional materials.